Réponses

2013-11-03T15:25:21+01:00
A) (-1) - 6.5 = 4*1+1 ensuite tu calcules
b) (-2) - 6,5 = 4* (-2) + 1 pareil
c) (-1,5) - 6.5 = 4* 1.5 + 1 pareil
Ah d'accord merci beaucoup mais les * siginifient quoi?
??
2013-11-03T15:39:54+01:00
A) -1 - 6,5 = -7,5
4 x (-1) + 1 = -4 + 1 = 3
L'égalité est est faux

b) -(-2) - 6,5 = -4,5
4 x (-2) + 1 = -8 + 1 = -7
L'égalité est faux.

c) -1,5 - 6,5 = -8
4 x 1,5 + 1 = 6 + 1 = 7
L'égalité est faux.

BONUS : 
-x - 6,5 = 4x + 1
-x - 4x = 6,5 + 1
-5x = 7,5
x = -1,5